A novel treatment protocol with 6 cycles of neoadjuvant chemotherapy followed by cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) in stage III primary ovarian cancer. (June 2021) - Marrelli, Daniele; Petrioli, Roberto; Cassetti, Dario; D'Ignazio, Alessia; Marsili, Stefania; Mazzei, Maria Antonietta; Lazzi, Stefano; Roviello, Franco
Abstract: Background: Few prospective studies investigated neoadjuvant chemotherapy (NAC), interval cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in advanced ovarian cancer. We report the results of a phase II study where 6 rather than 3 cycles of NAC, followed by CRS and HIPEC, were adopted (HIPEC_ovaio, EudraCT number 2007-005674-31). Materials and methods: Between 2007 and 2014, 56 patients with stage III primary ovarian cancer and peritoneal carcinomatosis were assigned to 6 cycles of platinum and taxane-based NAC. Of these, two had progression, 8 underwent palliative surgery, and 46 had CRS and HIPEC. Results: A complete pathological response was observed in 9 patients. Of 46 patients who completed the treatment protocol, 29 had no macroscopic residual tumor. Postoperative grade III morbidity rate was 28.2%; no grade IV complications or mortality events were observed. Five-year overall survival (OS) of the entire series was 36 ± 7% (median: 36, 95% CI: 26–45 months). In 46 patients treated by CRS and HIPEC, 5-year OS was 42 ± 8% (median: 53, 95% CI: 29–76 months), and 5-year progression-free survival was 26 ± 7% (median: 23, 95% CI: 19–27 months). Completeness of cytoreduction, peritoneal cancer index and FIGO stage resulted as significant prognostic factors. Conclusions: A novel protocol consisting of 6 cycles of NAC, followed by CRS and HIPEC, is associated with notable improvement in peritoneal carcinomatosis, limited postoperative morbidity risk and high survival rates in responders, and could deserve further investigations in randomized clinical trials. Highlights: Stage III primary ovarian cancer treated with neoadjuvant chemotherapy, CRS and HIPEC. Six rather than 3 cycles of neoadjuvant chemotherapy performed; 56 patients enrolled. High response rate, with 83.9% clinical response and 16.7% complete pathological response. Low grade III morbidity rate (28.2%); no grade IV complications, no mortality. Five-year OS of 42 ± 8% (median: 53 months) in 46 patients treated by CRS and HIPEC.